Effects of Organic Polymer Compound Material on K+ and Na+ Distribution and Physiological Characteristics of Cotton Under Saline and Alkaline Stresses - Wang, Xiaoli; An, Mengjie; Wang, Kaiyong; Fan, Hua; Shi, Jiaohua; Chen, Kuan (Frontiers in Plant Science, 2021)
Soil salinization and alkalization greatly restrict crop growth and yield. In this study, NaCl (8 g kg−1) and Na2CO3 (8 g kg−1) were used to create saline stress and alkaline stress on cotton in pot cultivation in the field, and organic polymer compound material (OPCM) and stem girdling were applied before cotton sowing and at flowering and boll-forming stage, respectively, aiming to determine the effects of OPCM on K+ and Na+ absorption and transport and physiological characteristics of cotton leaf and root. The results showed that after applying the OPCM, the Na+ content in leaf of cotton under saline stress and alkaline stress were decreased by 7.72 and 6.49%, respectively, the K+/Na+ ratio in leaf were increased by 5.65 and 19.10%, respectively, the Na+ content in root were decreased by 9.57 and 0.53%, respectively, the K+/Na+ ratio in root were increased by 65.77 and 55.84%, respectively, and the transport coefficients of K+ and Na+ from leaf to root were increased by 39.59 and 21.38%, respectively. The activities of superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD), and the relative electrical conductivity (REC) in cotton leaf were significantly increased, while the content of malondialdehyde (MDA) was decreased; but the changes in those in root were not significant. The boll weights were increased by 11.40 and 13.37%, respectively, compared with those for the control. After stem girdling, the application of OPCM still promoted the ion transport of cotton organs; moreover, the CAT activity in root was increased by 25.09% under saline stress, and the SOD activity in leaf and CAT in root were increased by 42.22 and 6.91%, respectively under alkaline stress. Therefore, OPCM can significantly change the transport of K+ and Na+ to maintain the K+ and Na+ homeostasis in leaf and root, and regulate physiological and biochemical indicators to alleviate the stress-induced damage. Besides, the regulation effect of OPCM on saline stress was better than that on alkaline stress.